PENGARUH FASADE BANGUNAN TERHADAP KARAKTER VISUAL KAWASAN (Studi Kasus: Pecinan Semarang, Malaysia Dan Singapura) - Arnis Rochma Harani; Ken Motic (Jurnal Pengembangan Kota, 2017)
An area, in this case a road corridor is expected to have its own distinctive character that has the image. One of the region that still famous with its distinctive character is the Chinatown area. However, the current physical development changes in Chinatown area, particularly on its building function may change the façade of the buildings. Hence, this article aims to explore the charateristic of façade in chinatown area with the case of Chinatown areas in Indonesia (Semarang city), Malaysia and Singapore. The exploration of these areas not previously been examined and contributes on the development of historic Chinatown area, particularly in Semarang. This study used a qualitative method with dependent indicator is a visual character, while the independent indicator is component of façade. This research found that the areas that still have strong visual character and still preserve the architectural character of the Chinese is Singapore Chinatown area, followed by Malaysia, and Semarang.